Biomechanical analysis of the stance phase during barefoot and shod running - de Wit, B.; de Clercq, D.; Aerts, P. (Journal of Biomechanics, 2000)
This study investigated spatio-temporal variables, ground reaction forces and sagittal and frontal plane kinematics during the stance phase of nine trained subjects running barefoot and shod at three different velocities (3.5, 4.5, 5.5 m s-1). Differences between conditions were detected with the general linear method (factorial model). Barefoot running is characterized by a significantly larger external loading rate than the shod condition. The flatter foot placement at touchdown is prepared in free flight, implying an actively induced adaptation strategy. In the barefoot condition, plantar pressure measurements reveal a flatter foot placement to correlate with lower peak heel pressures. Therefore, it is assumed that runners adopt this different touchdown geometry in barefoot running in an attempt to limit the local pressure underneath the heel. A significantly higher leg stiffness during the stance phase was found for the barefoot condition. The sagittal kinematic adaptations between conditions were found in the same way for all subjects and at the three running velocities. However, large individual variations were observed between the runners for the rearfoot kinematics.